Loka dhātʻ che" kyamʻʺ krī" nhaṅʻ' dhā tu pra sṃsa dhātʻ kyamʻʺ krī" (2) coṅʻ tvai - Ūʺ bhuiʺ lhuiṅʻ (Raṅʻ Kunʻ : Vṃ sā ra kkha piṭa katʻ puṃ nhipʻ tuikʻ, 1928)
Myanmar Traditional medicine and therapeutics.
Keywords: Traditional medicine -- Burma -- 19th century; Therapeutics -- Burma -- 19th century